2020
DOI: 10.3390/biology9080235
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 Protein Landscape in the Head and Neck Region: The Conundrum of SARS-CoV-2 Infection

Abstract: The coronavirus pandemic raging worldwide since December 2019 is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which invades human cells via the angiotensin-converting enzyme 2 (ACE2) receptor. Although it has already been identified in many organs, ACE2 expression remains largely unknown in the head and neck (HN) sphere. Thus, this study aims to investigate its protein expression in several sites of the upper aerodigestive tract in order to highlight potential routes of infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 61 publications
1
49
0
7
Order By: Relevance
“…Since the SARS-CoV-2 virus affects both upper and lower respiratory tracts one should expect that there would be multiple possible causes for the dysphonia with this viral infection. .It has been recently demonstrated that ACE2 is expressed in the epithelial cells of the vocal folds [11] , and that ACE2 is the receptor utilized by SARS-CoV-2 to penetrate human cells [ 6 , 11 ]. Therefore dysphonia might be caused by direct entry of SARS-CoV-2 into the glottic epithelium with consequent infection and damage.…”
Section: Discussionmentioning
confidence: 99%
“…Since the SARS-CoV-2 virus affects both upper and lower respiratory tracts one should expect that there would be multiple possible causes for the dysphonia with this viral infection. .It has been recently demonstrated that ACE2 is expressed in the epithelial cells of the vocal folds [11] , and that ACE2 is the receptor utilized by SARS-CoV-2 to penetrate human cells [ 6 , 11 ]. Therefore dysphonia might be caused by direct entry of SARS-CoV-2 into the glottic epithelium with consequent infection and damage.…”
Section: Discussionmentioning
confidence: 99%
“…21 Expression of ACE2 protein detected by polyclonal antibody revealed moderate to strong staining covering >75% of the epithelium of oral mucosa and salivary glands, and weak staining in fibroblasts and immune inflammatory cells of oral cavity. 22 Present in-silico analyses showed that miR-146 and miR-155 are widely involved in the regulation of cellular factors present in oral mucosa and important for SARS-CoV-2 entry. Regulation of essential viral receptor, ACE2, by miRs seems to be indirect, by suppressing co-expressed genes: miR-155 express high efficacy in targeting and suppressing AGTR1 expression while miR-146 suppresses gene expression of membrane metallo-endopeptidase (MME, neprilysin) and prolyl carboxypeptidase (PRCP).…”
Section: Gene Interaction Networkmentioning
confidence: 99%
“…The patient did not appear to have other common causes of PVFMD, including reflux, viral infection or psychological stress, which may support a potential association with COVID-19. The potential relationship between both conditions may be strengthened by the neuroinvasive potential of COVID-19 [3] and the vocal fold expression of ACE2 [4]. From a theoretical standpoint, the virus may spread into the tissue by the vocal fold ACE2 and may penetrate into the laryngeal nerve endings.…”
mentioning
confidence: 99%